PENGARUH LABEL HALAL, FOOD QUALITY DAN SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION - Sumardy, Karina Dewi; Marpaung, Nicholas; Dirbawanto, Nana Dyki (Talenta Publisher, 2022)
Pochajjang Korean Barbeque is one of the branches of Korean restaurants in Medan City which is currently developing. Based on observations, many responses from customers show that they are uncomfortable and even bad in terms of service and food quality. Consumers doubt the halalness of food ingredients due to several influencing factors such as the cheaper prices than the other restaurants with the same concept. This study aims to determine the influence of halal labels, food quality and service quality on customer satisfaction. This research method uses a quantitative method with an associative approach. A total of 96 respondents as the research sample. The data analysis technique used the IBM SPSS 20. The results showed that the halal label had a significant effect on customer satisfaction; food quality had a significant effect on customer satisfaction; and service quality had a significant effect on customer satisfaction. The coefficient value (R) is 0.854, and the R square value is 0.729. This value indicates that the three independent variables, namely halal label, food quality and service quality, simultaneously have an effect of 72.9% on the dependent variable, namely customer satisfaction. While the remaining 27.1% is influenced by other variables not included in this study.